Enthesitis: an obscured extraintestinal manifestation in pediatric inflammatory bowel disease - Gerenli, Nelgin; Sözeri, Betül (The Turkish Journal of Pediatrics, 2021)
Background. Enthesitis is an extra-intestinal manifestation of inflammatory bowel disease (IBD) which often remains underdiagnosed in children. We aimed to evaluate the frequency of enthesitis in pediatric IBD patients using physical examination and ultrasound (US) assessment as the reference standard. Methods. 31 children, 7 -18 years of age, diagnosed with IBD were recruited for a cross-sectional study. All subjects completed a study questionnaire and underwent both physical and US examination for the presence of the enthesitis. Results. Of 31 subjects (17girls; median age 14(6) years) enrolled, 17 (55%) had ulcerative colitis, 11 (35%) had Crohn`s disease, and 3 (10%) had indeterminate colitis. The median time from IBD diagnosis was 1.2 years. At least one enthesitis (range 1-4) was identified in 14 (45%) patients of whom nine had more than one enthesitis with symmetric involvement in eight. The quadriceps femoris insertion at the superior portion of the patella was the frequently involved site (32%, 9 of 28 sites), followed by patellar ligament insertion at tibial tuberositas. The presence of enthesitis was associated with a higher intensity of the musculoskeletal pain (p=0.018), but physical activity remained unaffected (p=0.056). Conclusions. Enthesitis is a common underestimated extra-intestinal manifestation of IBD that may impact the musculoskeletal health of children. Future studies with more extensive cohorts are needed to evaluate enthesial involvement both with physical examination and US in order to predict the long-term outcomes of the enthesitis on children with IBD.